2. INTERVENTION TO IMPROVE BONE DENSITY USING VITAMIN K2 SUPPLEMENTS IN POSTMENOPAUSAL WOMEN AGED 45 AND ABOVE IN LAM DONG PROVINCE IN 2023-2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: To evaluate the effectiveness of improving bone density through supplementation in postmenopausal women aged 45 and above in Lam Dong province in 2023-2024.Objects and methods: This community intervention study, monitored over 6 months was conducted among postmenopausal women aged 45 and above with osteopenia. The intervention group I received supplements of vitamin K2, calcium, and vitamin D3, while intervention group II received calcium and vitamin D3 supplements.Results: In intervention group I, the average Osteocalcin index decreased from 21.08 ± 10.39 ng/mL to 18.28 ± 8.08 ng/mL (p < 0.001); similarly, intervention group II also recorded a decrease in Osteocalcin index from 21.42 ± 6.83 ng/mL to 19.29 ± 6.77 ng/mL (p = 0.003). For β-CTX index, intervention group I decreased from 351.27 ± 177.05 ng/mL to 236.78 ± 129.19 ng/mL (p < 0.001); meanwhile, intervention group II decreased from 298.58 ± 141.82 ng/mL to 284.61 ± 170.90 ng/mL, but the difference was not statistically significant (p = 0.568).Conclusions: Supplementing vitamin K2 combined with calcium and vitamin D3 significantly changed bone turnover markers compared to the group supplementing only calcium and vitamin D3.
Keywords: Bone density reduction; nutritional products; vitamin K2; postmenopausal women; Lam Dong